Prospects for gamma-ray observations of narrow-line Seyfert 1 galaxies with the Cherenkov Telescope Array. Issue 4 (10th September 2018) - Romano, P; Vercellone, S; Foschini, L; Tavecchio, F; Landoni, M; Knödlseder, J
ABSTRACT: Gamma-ray-emitting narrow-line Seyfert 1 (γ-NLS1) galaxies are thought to harbour relatively low-mass black holes (10 6 –10 8 M ) accreting close to the Eddington limit. They show characteristics similar to those of blazars, such as flux and spectral variability in the gamma-ray energy band and radio properties which point towards the presence of a relativistic jet. These characteristics make them an intriguing class of sources to be investigated with the Cherenkov Telescope Array (CTA), the next-generation ground-based gamma-ray observatory. We present our extensive set of simulations of all currently known γ-ray emitters identified as NLS1s (20 sources), investigating their detections and spectral properties, taking into account the effect of both the extragalactic background light in the propagation of gamma-rays and intrinsic absorption components. We find that the prospects for observations of γ-NLS1 with CTA are promising. In particular, the brightest sources of our sample, SBS 0846+513, PMN J0948+0022, and PKS 1502+036, can be detected during high/flaring states, the former two even in the case in which the emission occurs within the highly opaque central regions, which prevent gamma-rays above a few tens of GeV to escape. In this case, the low-energy threshold of CTA will play a key role. If, on the other hand, high-energy emission occurs outside the broad-line region, we can detect the sources up to several hundreds of GeV – depending on the intrinsic shape of the emitted spectrum. Therefore, CTA observations will provide valuable information on the physical conditions and emission properties of their jets.